Sleep medicine: Practice, challenges and new frontiers - Parrino, Liborio; Halasz, Peter; Szucs, Anna; Thomas, Robert J.; Azzi, Nicoletta; Rausa, Francesco; Pizzarotti, Silvia; Zilioli, Alessandro; Misirocchi, Francesco; Mutti, Carlotta (Frontiers in Neurology, 2022)
Sleep medicine is an ambitious cross-disciplinary challenge, requiring the mutual integration be-tween complementary specialists in order to build a solid framework. Although knowledge in the sleep field is growing impressively thanks to technical and brain imaging support and through de-tailed clinic-epidemiologic observations, several topics are still dominated by outdated paradigms. In this review explore the main novelties and gaps in the field of sleep medicine, assess the common-est sleep disturbances, provide advices for routine clinical practice and offer alternative insights and perspectives on the future of sleep research.